Answer: A
Step-by-step explanation:
Sally: 66/3=22
Molly: 72/4=18
22-18=4
The standard form: Ax + By = C
3x - y = -6 YES - A = 3, B = -1, C = -6
3x + y = 6 YES - A = 3, B = 1, C = 6
x + 6y = 9 YES - A = 1, B = 6, C = 9
x - 6y = -9 YES - A = 1, B = -6, C = -9
Answer:
y = -2x - 7
Step-by-step explanation:
x - 2y = 6
-2y = -x + 6
Divide the whole equation by (-2)
![\frac{-2y}{-2}=\frac{-x}{-2}+\frac{6}{-2}\\\\y = \frac{1}{2}x - 3](https://tex.z-dn.net/?f=%5Cfrac%7B-2y%7D%7B-2%7D%3D%5Cfrac%7B-x%7D%7B-2%7D%2B%5Cfrac%7B6%7D%7B-2%7D%5C%5C%5C%5Cy%20%3D%20%5Cfrac%7B1%7D%7B2%7Dx%20-%203)
slope = 1/2
Slope of the line perpendicular to this line = -1/m = -1 ÷ (1/2)
![=(-1)*\frac{2}{1}\\\\= -2](https://tex.z-dn.net/?f=%3D%28-1%29%2A%5Cfrac%7B2%7D%7B1%7D%5C%5C%5C%5C%3D%20-2)
(-3, - 1)
y -y1 = m(x -x1)
y - [-1] = -2(x - [-3])
y + 1 = -2(x + 3)
y + 1= x* (-2) + 3*(-2)
y + 1 = -2x - 6
y = -2x - 6 - 1
y = -2x - 7
take square root and subtract y2 from y1 and x2 from x1